ANALISIS AKAD PEMBIAYAAN MUDHARABAH DAN IMPLIKASINYA TERHADAP KESEJAHTERAAN ANGGOTA DALAM PERSPEKTIF EKONOMI SYARI’AH (Studi Kasus di Kopwan BMT An Nisa Yogyakarta 2013) - Muhammad Ngasifudin; Abdul Salam (JESI (Jurnal Ekonomi Syariah Indonesia), 2015)
Abstract Vision and Mission Suitability Kopwan BMT An-Nisa ‘is a good partner for a whole by using the principle of sharing (proﬁ t sharing) because of the characteristics common to Kopwan BMT An-Nisa’ TOTAL LIABILITY such as mudaraba ﬁ nancing, the bank mechanism Shari’ah applies to products ﬁ nancing-products. The parties involved in this case have to do transparency and partnership are good and relaxed and able to provide a sense of peace to the members. Because all of the expenses and income with business berkitan routine. Financing is in Kopwan BMT An-Nisa ‘is constantly increasing, this study to describe bertujaun of ﬁ nancing, the system of ﬁ nancing and results on the impact of the ﬁ nancing is for the welfare of members. In this case study using qualitative research methods with descriptive approach, to obtain data through observation, interviews and documentation, analysis of the data obtained, collected, processed, analyzed and then matched with the concept and application of ﬁ nancing on Kopwan BMT An-Nisa ‘interpretation and reviewing pull back later at a conclusion and give suggestions. Keywords: mudaraba ﬁ nancing, proﬁ t and lose sharing, welfare (Fallah)